IgA Nephropathy Associated with IgA Vasculitis Coexisting with Focal Segmental Glomerulosclerosis Tip Variant: A Case Report (Journal of Renal and Hepatic Disorders, 2023)
IgA vasculitis (IgAV), previously known as Henoch–Schönlein purpura, is a form of small vessel vasculitis that affects the skin, joints, intestines, and kidneys. The clinical presentation in adults is usually infrequent, more severe, with a worse prognosis and a higher recurrence rate. Due to limited scientific evidence, IgAV is viewed similarly to IgA nephropathy (IgAN), and the renal histopathological lesions are indistinguishable between the two. IgAN is the most prevalent glomerular diseases worldwide. The diagnosis of IgAN is confirmed through a renal biopsy. The most frequently found histopathological lesions are mesangial proliferation and concurrent IgA deposition confirmed by direct immunofluorescence. Focal segmental glomerulosclerosis (FSGS) appears as a glomerular pattern of injury in up to 40% of renal biopsies with IgAN, although there are few reported cases in the international literature where both diseases coexist as primary etiologies. We report a case of a female patient presenting with vasculitic lesions, abdominal pain, and nephrotic syndrome, whose cause is confirmed by a renal biopsy with a diagnosis of IgAN secondary to IgAV and coexistence of FSGS, an unusual presentation with few case reports.
Keywords: glomerulosclerosis; IgA nephropathy; IgA vasculitis; nephrotic syndrome